2017
DOI: 10.1103/physrevb.95.174515
|View full text |Cite
|
Sign up to set email alerts
|

Transport in superconductor–normal metal–superconductor tunneling structures: Spinful p -wave and spin-orbit-coupled topological wires

Abstract: We theoretically study transport properties of voltage-biased one-dimensional superconductornormal metal-superconductor tunnel junctions with arbitrary junction transparency where the superconductors can have trivial or nontrivial topology. Motivated by recent experimental efforts on Majorana properties of superconductor-semiconductor hybrid systems, we consider two explicit models for topological superconductors: (i) spinful p-wave, and (ii) spin-split spin-orbit-coupled s-wave. We provide a comprehensive ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…20,21 Since Majorana fermions follow non-Abelian statistics and are their own antiparticles, superconducting Weyl systems are anticipated to play a promising role in topological quantum computing. [22][23][24][25] Experimentally, superconductivity in Weyl materials has been discovered in a variety of settings, including in MoTe 2 under pressure, and in TaAs by photoemission spectroscopy. 26,27 It was reported that surface superconductivity can be induced in NbAs through ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Since Majorana fermions follow non-Abelian statistics and are their own antiparticles, superconducting Weyl systems are anticipated to play a promising role in topological quantum computing. [22][23][24][25] Experimentally, superconductivity in Weyl materials has been discovered in a variety of settings, including in MoTe 2 under pressure, and in TaAs by photoemission spectroscopy. 26,27 It was reported that surface superconductivity can be induced in NbAs through ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, information on the spin canting angle of the MBS can be extracted using this Majorana non-locality [29,31]. Junctions consisting of a conventional s-wave (BCS) lead and a TSC have also been in the focus of some investigations where most of the works address on non-equilibrium transport [33][34][35][36][37]. For a pure s-wave-p-wave junction it was concluded that the supercurrent is blocked [38].…”
mentioning
confidence: 99%
“…Surface Andreev bound states must occur in p -wave topological superconductors 41 . Moreover, based on the phase-changing quasiparticle reflections at the p -wave surface, finite-energy Andreev resonances should also occur in the junction between a p -wave and an s -wave superconductor 42 and are observed in UTe 2 . Inside the SIS gap, we measure the map in the energy range from −500 µeV to 500 µeV.…”
Section: Methodsmentioning
confidence: 99%